Variable frequency of LRRK2 variants in the Latin American research consortium on the genetics of Parkinson's disease (LARGE-PD), a case of ancestry (2017)
ABSTARCT: Mutations in Leucine-Rich Repeat Kinase 2 (LRRK2), primarily located in codons G2019 and R1441, represent the most common genetic cause of Parkinson's disease in European-derived populations. However, little is known about the frequency of these mutations in Latin American populations. In addition, a prior study suggested that a LRRK2 polymorphism (p.Q1111H) specific to Latino and Amerindian populations might be a risk factor for Parkinson's disease, but this finding requires replication. We screened 1734 Parkinson's disease patients and 1097 controls enrolled in the Latin American Research Consortium on the Genetics of Parkinson's disease (LARGE-PD), which includes sites in Argentina, Brazil, Colombia, Ecuador, Peru, and Uruguay. Genotypes were determined by TaqMan assay (p.G2019S and p.Q1111H) or by sequencing of exon 31 (p.R1441C/G/H/S). Admixture proportion was determined using a panel of 29 ancestry informative markers. We identified a total of 29 Parkinson's disease patients (1.7%) who carried p.G2019S and the frequency ranged from 0.2% in Peru to 4.2% in Uruguay. Only two Parkinson's disease patients carried p.R1441G and one patient carried p.R1441C. There was no significant difference in the frequency of p.Q1111H in patients (3.8%) compared to controls (3.1%; OR 1.02, p = 0.873). The frequency of LRRK2-p.G2019S varied greatly between different Latin American countries and was directly correlated with the amount of European ancestry observed. p.R1441G is rare in Latin America despite the large genetic contribution made by settlers from Spain, where the mutation is relatively common.